2014
DOI: 10.1055/s-0034-1378138
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Options in Idiopathic Burning Mouth Syndrome: Literature Review

Abstract: Introduction Burning mouth syndrome (BMS) is characterized by a burning sensation in the tongue, palate, lips, or gums of no well-defined etiology. The diagnosis and treatment for primary BMS are controversial. No specific laboratory tests or diagnostic criteria are well established, and the diagnosis is made by excluding all other possible disorders. Objective To review the literature on the main treatment options in idiopathic BMS and compare the best results of the main studies in 15 years. Data Synthesis W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 27 publications
2
27
2
3
Order By: Relevance
“…In addition, patients demonstrating symptom reduction but not total or adequate resolution may benefit from psychological intervention to supplement medical/dental treatment. Although cognitive behavioral therapies have been recommended as part of a multidisciplinary intervention for BMS patients, the empirical literature regarding the effectiveness of psychological interventions is limited to studies of group therapies [63,64]. For example, in an early study, BMS patients were randomized into a cognitive therapy group that met weekly for 12 weeks to 15 weeks or into an attention control group [65].…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…In addition, patients demonstrating symptom reduction but not total or adequate resolution may benefit from psychological intervention to supplement medical/dental treatment. Although cognitive behavioral therapies have been recommended as part of a multidisciplinary intervention for BMS patients, the empirical literature regarding the effectiveness of psychological interventions is limited to studies of group therapies [63,64]. For example, in an early study, BMS patients were randomized into a cognitive therapy group that met weekly for 12 weeks to 15 weeks or into an attention control group [65].…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…Thus, the patients are oriented with several therapies, with results not always satisfactory that vary from tongue protectors to prescription drugs 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to minimize the adverse effects, the use of topical clonazepan was evaluated, with reduction of 70% in the burning sensation 15 . However, the study performed by Moraes et al 16 observed that even in topical form, some patients reported side effects, such as drowsiness, xerostomia, and increased burning sensation in the mouth in some cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two variants of BMS have been described, the primary form, which is idiopathic and is defined according to the criteria above, and the secondary form, which is observed when a local or systemic causal agent is present [2][3][4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%